Superiority Theory and Disparagement Humor: The Role of Gelotophobia, Gelotophilia, and Katagelasticism - Voutsa, Maria C.; Hatzithomas, Leonidas; Boutsouki, Christina (My University, 2018)
Risky communication strategy though it is, disparagement humorous advertising has proliferated over the last decades (Gulas et al., 2010; Weinberger et al., 2015). Although humorous advertisements are generally known to have a positive effect on attitude toward the ad (Duncan and Nelson, 1985; Eisend, 2008; Venkatesh and Senthilkumar, 2015; Weinberger and Gulas, 1992), highly disparaging humorous advertisements may lead to adverse consumer reactions (Cho, 1995). Consumers seem to form a positive attitude toward the disparaging humorous advertisements only when the latter are perceived as very humorous (Brown et al., 2010; Newton et al., 2016; Yoon, 2016).
Keywords: Superiority theory; Gelotophobia; Gelotophilia; Katagelasticism; Humorous advertisement